Effects of Age and Gender on Hand Motion Tasks - Wing Lok Au; Irene Soo Hoon Seah; Wei Li; Louis Chew Seng Tan (Parkinson's Disease)
Objective. Wearable and wireless motion sensor devices have facilitated the automated computation of speed, amplitude, and rhythm of hand motion tasks. The aim of this study is to determine if there are any biological influences on these kinematic parameters. Methods. 80 healthy subjects performed hand motion tasks twice for each hand, with movements measured using a wireless motion sensor device (Kinesia, Cleveland Medical Devices Inc., Cleveland, OH). Multivariate analyses were performed with age, gender, and height added into the model. Results. Older subjects performed poorer in finger tapping (FT) speed (r=0.593, p<0.001), hand-grasp (HG) speed (r=0.517, p<0.001), and pronation-supination (PS) speed (r=0.485, p<0.001). Men performed better in FT rhythm p<0.02, HG speed p<0.02, HG amplitude p<0.02, and HG rhythm p<0.05. Taller subjects performed better in the speed and amplitude components of FT p<0.02 and HG tasks p<0.02. After multivariate analyses, only age and gender emerged as significant independent factors influencing the speed but not the amplitude and rhythm components of hand motion tasks. Gender exerted an independent influence only on HG speed, with better performance in men p<0.05. Conclusions. Age, gender, and height are not independent factors influencing the amplitude and rhythm components of hand motion tasks. The speed component is affected by age and gender differences.